Analysis Of Factors Influencing New Vehicle Purchase Descicions At Auto200 Bukittinggi - Sabri; Mairinal Avis; Melianus Lase (PT. Padang Tekno Corp, 2026)
The study aims to see factors that influence the decision to purchase new vehicles in Auto2000 Bukittinggi of motivations, perceptions, learning, economic circumstances and lifestyle. The population in this study is 213 people and 70 people are sample material. Data is collected through the distribution of questionnaires with a likert scale model and then tested to the validity and reliability of the questionnaire. The data analysis technique used isa factor analysis method using the SPSS program 23.00. The purpose of this factor's analysis is to see what factors influence the decision to buy new vehicles in Auto2000 Bukittinggi and at the same time see the most dominant factor. Analysis has found that motivational, perceptions, learning, economic circumstances and lifestyle are positive for new vehicle purchase decisions in Auto2000 Bukittinggi and the most dominant factor is economic circumstances.